The evolutionary convergence of mid-Mesozoic lacewings and Cenozoic butterflies - Labandeira, Conrad C. (Proc Biol Sci, 2016)
Mid-Mesozoic kalligrammatid lacewings (Neuroptera) entered the fossil record 165 million years ago (Ma) and disappeared 45 Ma later. Extant papilionoid butterflies (Lepidoptera) probably originated 80–70 Ma, long after kalligrammatids became extinct. Although poor preservation of kalligrammatid fossils previously prevented their detailed morphological and ecological characterization, we examine new, well-preserved, kalligrammatid fossils from Middle Jurassic and Early Cretaceous sites in northeastern China to unravel a surprising array of similar morphological and ecological features in these two, unrelated clades. We used polarized light and epifluorescence photography, SEM imaging, energy dispersive spectrometry and time-of-flight secondary ion mass spectrometry to examine kalligrammatid fossils and their environment. We mapped the evolution of specific traits onto a kalligrammatid phylogeny and discovered that these extinct lacewings convergently evolved wing eyespots that possibly contained melanin, and wing scales, elongate tubular proboscides, similar feeding styles, and seed–plant associations, similar to butterflies. Long-proboscid kalligrammatid lacewings lived in ecosystems with gymnosperm–insect relationships and likely accessed bennettitalean pollination drops and pollen. This system later was replaced by mid-Cretaceous angiosperms and their insect pollinators.